Similarity model test and numerical simulation of double parallel-tunnel excavation in hard rock under high ground-stress conditions - ZHAO Yu-song; GAO Yong-tao; SONG Wei-chao (工程科学学报)
Based on the similarity simulation theory, a parallel-tunnel model test system was constructed that consists of a test bench design, a monitoring system design, a loading system design, and the construction of a rock mass model. The models were monitored in key positions of displacement, stress changes, and destruction of the tunnel walls. It is found that the experimental observation and numerical simulation results based on the Mohr-Coulomb model exhibit relatively large disparities. However, based on the Plastic-Hardening model, the yield states and variation laws of the rock and soil were obtained by numerical simulation and these results are in good agreement with the experimental results. If all aspects of research results is integrated, the Plastic-Hardening model accurately reflects real changes in the states of the rock and soil in actual engineering applications and tests and can provide an important reference for double parallel-tunnel construction and maintenance under similar geological conditions.